2019
DOI: 10.1098/rsif.2018.0776
|View full text |Cite
|
Sign up to set email alerts
|

Going with the flow: hydrodynamic cues trigger directed escapes from a stalking predator

Abstract: In the coevolution of predator and prey, different and less well-understood rules for threat assessment apply to freely suspended organisms than to substrate-dwelling ones. Particularly vulnerable are small prey carried with the bulk movement of a surrounding fluid and thus deprived of sensory information within the bow waves of approaching predators. Some planktonic prey have solved this apparent problem, however. We quantified cues generated by the slow approach of larval clownfish (Amphiprion ocellaris) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 67 publications
2
20
0
Order By: Relevance
“…In those cases, the hydrodynamic signal available to the copepod was weaker, resulting in a late escape response and a shorter reaction distance to the approaching predator (Viitasalo et al 1998). Similar results were observed for Amphiprion ocellaris larvae feeding on the calanoid copepod Bestiolina similis (Tuttle et al 2019). In the present study we found an opposite trend: feeding success was limited to cases in which the larvae swam quickly towards the prey.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In those cases, the hydrodynamic signal available to the copepod was weaker, resulting in a late escape response and a shorter reaction distance to the approaching predator (Viitasalo et al 1998). Similar results were observed for Amphiprion ocellaris larvae feeding on the calanoid copepod Bestiolina similis (Tuttle et al 2019). In the present study we found an opposite trend: feeding success was limited to cases in which the larvae swam quickly towards the prey.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies of feeding success by larval fish have focused on their interactions with non-evasive prey (Hernández 2000; Krebs and Turingan 2003; China and Holzman 2014; China et al 2017) although several studies have reported on interactions between copepods and clownfish larvae (Jackson and Lenz 2016; Robinson et al 2019; Tuttle et al 2019). In small marine larvae that hatch from pelagic eggs, the hydrodynamic environment (denoted by Re) is the dominant factor that determines larval kinematics and prey capture performance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations